Symphony in the Flint Hills - 2010 Artists; Limited Edition Art Print (Symphony in the Flint Hills, 2010)
List of the artists and works contributed for the annual silent auction. And the Limited Edition Art Print by Deb Schroer
Keywords: paintings; Flint Hills; artists; prints; auction; Deb Schroer; Drama at Sunset